FORMULASI LOTION TABIR SURYA EKSTRAK ETANOL BERAS MERAH (Oryza nivara) - Nur Saadah Daud; La Ode Zahid Al Hajri N.S; Ervianingsih (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
Sunburn, premature aging and skin cancer due to the exposure of UV radiation especially UVA and UVB, became one of the causes the cosmetic products commercialization containing sunscreen compound increase. Red rice as one of the natural ingredient was reported have sunscreen activity as its containing anthocyanin pigments. This study was conducted to formulate the ethanolic extract of red rice into the sunscreen lotion form that has the sunscreen activity and stable. The extraction was done using maceration method with 96% ethanol as a solvent. Pysical stability and sunscreen effectiveness studies were done to the three formula lotions containing ethanolic extract respectively of 2.5% (Formula A), 5% (Formula B) and 10% (Formula C). All lotions were scented of typical rose oil in semi-solid form with an average value of viscosity were of 90-100 dPa.s. The sunscreen lotions were colored white to white dark peach. The studies showed the stability of all lotion preparations remained homogeneous and did not undergo a phase inversion with the emulsion type of oil in water (O/W) through cycling test. Unfortunately the distinctive odor of rose oil were reduced and the dosage form became more dilute caused the spread force became larger. The studies also showed the sunscreen effectiveness of SPF values were increase as the increasing of the extract concentration. The SPF value for each formula were 5.30 (moderate protection), 6.30 (extra protection) and 7.00 (extra protection). The base components of lotion did not affect the sunscreen activity with SPF values of 1.76 (not effective).